2013
DOI: 10.1155/2013/658638
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making about Risk of Infection by Young Adults with CF

Abstract: Young people with cystic fibrosis (CF) are asked to avoid a number of environments associated with increased infection risk, but in practice they need to balance this with competing priorities such as building and sustaining relationships with friends and family. This study explored the process by which young people make these decisions. Mixed methods were used: a vignette study presenting choices around engaging in activities involving a degree of infection risk and a thematic analysis of participant's accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The survey recorded participants' self-reported demographics (age, gender, height, and FEV1%) and their decisions about courses of action in four vignettes adapted from our qualitative study 13 . These were based on current IPC guidelines 1 …”
Section: Measures and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey recorded participants' self-reported demographics (age, gender, height, and FEV1%) and their decisions about courses of action in four vignettes adapted from our qualitative study 13 . These were based on current IPC guidelines 1 …”
Section: Measures and Methodsmentioning
confidence: 99%
“…In our previous qualitative work 13 , eight young adults with CF were shown infectionrelated social vignettes and asked to discuss their decision-making about associated risks.…”
Section: Introductionmentioning
confidence: 99%
“…"At the end of the day you cannot sort of shut yourself away....I think it' s really important to think about infection, but I think some people could take it too far." 95 Transplant expectations and uncertainty Confirmed severity of disease "Being listed [for transplant] signified a point in the chronic illness trajectory at which there was no longer any advantage in delaying the transplant procedure." 37 …”
Section: Financial Strainmentioning
confidence: 99%
“…The acceptance of risk however is a very individual decision, and views on risk of infection in any particular situation will differ from person to person. One interview-based study explored the views of a small number of young people with CF on risk of infection posed by a number of different scenarios [68]. The investigators identified that knowledge varied around potential risk for infection, but also individuals displayed different attitudes to approach of risk, often weighing risk of infection against the potential benefits of engaging in an activity and their desired lifestyle.…”
Section: Infection Risk: Patient Viewsmentioning
confidence: 99%